Development of Flashcard and Interactive Mind Mapping Media in The Website on Plant Tissue Material to Improve Student’s Comprehension and Motivation - Faradiba Widiasti; Isnawati Isnawati (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2023)
Pandemic conditions cause students to do most of their activities, including learning, at home. As a consequence of the monotonous online learning activities, student learning results decrease, and learning motivation suffers. Plant tissue material is one of the materials that is difficult to learn and require special attention because when the object of observation is difficult to sense, complicated, and it is not enough to simply study theoretically, but to learn in an applied and interactive way. The aim of the research is to develop plant tissue flashcard media and interactive website-based mind mapping as practical learning media to improve students' understanding and motivation. The ADDIE development model is used in this research (Analysis, Design, Implementation, and Evaluation). Validation methods, pretest and posttests, student response questionnaires, and student motivation questionnaires were used to collect data from 20 students in class 11, 8th Public High School of Surabaya. The information gathered was analyzed using descriptive-quantitative methods. The findings showed that flashcard and mind mapping media were highly valid, with a validity score of 3.97, could improve students' comprehension with a medium score, and received a 95.9% positive reaction from students. As an outcome, the website's interactive flashcard and mind mapping media on the plant tissue material provided are valid, practical, and useful in increasing comprehension. Keywords: flashcard, interactive mind mapping, website, plant tissue, learning comprehension, motivation.